Strain-specific interspecies interactions between co-isolated pairs of Staphylococcus aureus and Helcococcus kunzii from chronic wounds - Riham Daher; Benjamin A.R.N. Durand; Madjid Morsli; Cassandra Pouget; Jean-Philippe Lavigne; Catherine Dunyach-Remy (BMC Microbiology)
Abstract Background Bacterial infection is major contributor in the delay of wound healing and persistence of non-healing wounds. Bacteria, functioning within complex multicellular communities, facilitate the survival of certain microorganisms in diverse environments. Helcococcus kunzii, a Gram-positive anaerobic commensal coccus, and Staphylococcus aureus, the primary pathogen in chronic wounds, have strong interaction potential, in which H. kunzii decreases the virulence of S. aureus in co-culture in vivo and in vitro. Results This paper describes the interaction between H. kunzii and S. aureus clinical strains from chronic wounds by examining their transcriptomic behavior (S. aureus virulence genes) and phenotypic features (hemolysin production, growth and biofilm formation). We used five new clinical pairs of H. kunzii and S. aureus strains co-isolated from diabetic foot ulcers (DFU) and one previously studied clinical pair, not co-isolated from the same DFU. H. kunzii strains were sequenced and compared with two H. kunzii strains previously sequenced with high (H13) or low (H10) impact on S. aureus regulatory virulence effectors. Sequencing showed that all strains were phylogenetically similar to H13, with the exception of NHKT2, allowing to predict a potential “high impact” on S. aureus virulence. After coculture of clinical strain pairs in medium reflective of a chronic wound environment, we observed a downregulation of agrA and hla, two regulatory and virulence genes of S. aureus, supporting previously results obtained with not co-isolated strains. We confirmed a decrease in S. aureus hemolysin production in cocultures. While coculture did not affect the growth of S. aureus, the presence of H. kunzii appeared to influence the dynamics of S. aureus biofilm formation. Specifically, we noted a significant increase in S. aureus biofilm formation in coculture compared to monoculture during the biofilm maturation stage (after 72 h) for 4/5 of the co-isolated pairs. Conclusions The effect of reducing the virulence of S. aureus by H. kunzii described previously is not reproducible with co-isolated strains from same DFU. The therapeutic strategy of using H. kunzii as a probiotic should be reconsidered in favor of an approach that targets the underlying mechanisms responsible for this virulence reduction.